Anda di halaman 1dari 4

8-2 Factoring Using the Distributive Property

Recall using the distributive property for multiplying a monomial by a polynomial:

x(a + b) = ax + bx

Doing this produces a common factor in each term. In the above case that
common factor is x.

We can use this fact to help us factor polynomials that have a common factor in
all of their terms.

For example, the terms in the polynomial: 12a 2 +16a have a common factor, this
common factor is 4a (it is the GCF).

We can factor this polynomial by €


“undoing” the distributive property and factor out
the GCF:€

12a 2 +16a = 4a(3a + 4)

We can check our answer by simply using the distributive property to multiply.

Example: Factor 18cd 2 +12c 2 d + 9cd

1. The GCF of all the terms is 3cd , so divide all of the terms by 3cd
2. 3cd(6d
€ + 4c + 3)
3. Check by multiplying: 3cd(6d + 4c + 3) = 18cd 2 +12c 2 d + 9cd , this is correct.
€ €
Using Grouping to Factor


Sometimes all of the terms in a polynomial do not have a GCF, but pairs of terms
do. When this is the case we can use grouping to factor.

Example: Factor 4ab + 8b + 3a + 6

Notice that all of the terms do not have a GCF, but the first two and the last two
terms do. We € can group them in the following way:
(4ab + 8b) + (3a + 6) We can now factor each binomial separately:

4b(a + 2) + 3(a + 2) Now notice that each has a factor of (a + 2) , factor again:

(a + 2)(4b + 3) Done.
€ €


Example: Factor 6x 2 −15x − 8x + 20

We can group this polynomial like this: (6x 2 −15x) + (−8x + 20)

Factor each binomial: 3x(2x − 5) + −4(2x − 5)
Notice that I factored a -4 out of the second binomial instead
of a€4, why? So the resulting binomial would match the first one.

Notice that each now


€ has a factor of (2x − 5) , factor again:

(2x − 5)(3x − 4)

Check the answer by multiplying using the FOIL method:

2x(3x) − 2x(4) − 5(3x) + 5(4) = 6x 2 − 8x −15x + 20 , this is correct!
F O I L

Example: Factor rs + 5s − r − 5

We can group this polynomial like this: (rs − r) + (5s − 5) {I rearranged the terms}

Now factor each binomial: r(s −1) + 5(s −1)

€ of (s −1) , factor again:


Notice that each now has a factor

(s −1)(r + 5)

Check the answer by multiplying using the FOIL method:

rs + 5s −1r − 5 = rs + 5s − r − 5 , this is correct!
F O I L

Example: Factor 35x − 5xy + 3y − 21



We can group this polynomial like this: (35x − 5xy) + (3y − 21)

Now factor each binomial: 5x(7 − y) + 3(y − 7)

Notice that the resulting binomials are not the same, but they are almost the
same…we can make them the same by factoring a -1 out of the first binomial:

5x(−1)(−7 + y) + 3(y − 7) = −5x(y − 7) + 3(y − 7) Now the binomials match, factor
again:

(y − 7)(−5x + 3) This is correct.



Example: Factor c − 2cd + 8d − 4

1.Group the terms: (c − 2cd) + (8d − 4)


2.Factor
€ each binomial: c(1 − 2d) + 4(2d −1)
3.Factor a -1 out of the first binomial: c(−1)(−1+ 2d) + 4(2d −1)
4.Simplify −c(2d −1) + 4(2d −1)

5.Factor out (2d-1) (2d −1)(−c + 4)


Example: Factor 3p − 2 p 2 −18 p + 27


1. Group the terms: (3p − 2 p 2 ) + (−18 p + 27)
2. Factor
€ each binomial: p(3 − 2 p) + 9(−2 p + 3)
3. Rearrange the terms: p(3 − 2 p) + 9(3 − 2 p)
4. Factor out (3-2p) € (3 − 2 p)( p + 9)


Solving Equations by Factoring:

We can use factoring to help us solve equations. To do this we will use the Zero
Product Property.

The Zero Product Property states that if two things multiply to get zero, one or
both of them MUST be equal to zero.

If ab = 0 then either a = 0, b = 0, or a & b = 0

The solutions to an equation are called roots.


€ €
For example, if we have the equation x(x −1) = 0 we can say one of two things:
1. x = 0
or
2. x −1 = 0


So we can say that this equation has two solutions, or roots.

Either x = 0 or x = 1


Example: Solve the equation (d − 5)(3d + 4) = 0

Because of the Zero Product Property (ZPP) we can say one of two things:
1. d − 5 = 0

2. 3d + 4 = 0

€ Letʼs solve both of these scenarios to find the roots



3d + 4 = 0
d −5 =0 4
1. 2. 3d = −4 Therefore, d = 5 or −
d =5 3
4
d=−
3

€ Example: Solve the equation x 2 = 7x €


In order to use the ZPP, weʼll have to set one side of the equation to zero:

x 2 − 7x = 0

Now factor the binomial: x(x − 7) = 0



Now we can use the ZPP to say one of two things:
1. x = 0

2. x − 7 = 0

€ Letʼs solve both of the scenarios to find the roots



x −7=0
1. x = 0 2. Therefore, x = 0 or x = 7
x=7

Example: Solve the equation x 2 = −10x


€ €

In order to use the ZPP, weʼll have to set one side of the equation to zero:

x 2 +10x = 0

Now factor the binomial: x(x +10) = 0



Now we can use the ZPP to say that 1. x = 0 2. x +10 = 0
Now find the roots

x +10 = 0
1. x = 0 2. € Therefore,
€ x = 0 or −10
x = −10

€ €